Moving beyond ethnicity: the socio-economic status and living conditions of immigrant children in the UK - Heaven Crawley (Child Indicators, 2010)
This paper examines the situation of children in immigrant families living in the UK through an analysis of 2001 census data according to the country of birth of children and their parents. The foreign-born population in the United Kingdom reached 4.9 million in 2001, representing 8.3 per cent of the total population. Around 2.1 million children (16.3 per cent of all children in the UK) were living in immigrant families. A fifth of these children were born outside the UK with the remainder being born in the UK with at least one foreign-born parent. More than 40 per cent were in families from Asia, around 20 per cent from Africa and around 20 per cent from countries in Europe. Pakistan, India, the Republic of Ireland, Germany and Bangladesh were the main countries of origin. Although there is significant variation in the socioeconomic status and living conditions of immigrant families from different regions and countries of origin, it is clear that immigrant children are faring less well overall than their native-born counterparts. Levels of employment are higher among the parents of native-born children despite the fact that parents in immigrant families generally exhibit higher educational attainment levels. Immigrant children are more likely to be living in overcrowded housing that is not owned. The analysis presented in this paper suggests that an ethnicityfocused approach alone is inadequate for addressing the present and future needs of immigrants and their children or in understanding the dynamics of immigrant inclusion and exclusion.